2022
DOI: 10.3390/biomedicines10081943
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism in Glioblastoma: From De Novo Synthesis to Storage

Abstract: Glioblastoma (GBM) is the most lethal primary brain tumor. With limited therapeutic options, novel therapies are desperately needed. Recent studies have shown that GBM acquires large amounts of lipids for rapid growth through activation of sterol regulatory element-binding protein 1 (SREBP-1), a master transcription factor that regulates fatty acid and cholesterol synthesis, and cholesterol uptake. Interestingly, GBM cells divert substantial quantities of lipids into lipid droplets (LDs), a specific storage or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 269 publications
0
29
0
1
Order By: Relevance
“…However, this is a vast oversimplification of these pathways, and a more detailed review of SREBP-1 and FAS in GBM can be found in refs. 32 and 33 .…”
Section: The Four Categories Of Fa Metabolism In Gbmmentioning
confidence: 99%
“…However, this is a vast oversimplification of these pathways, and a more detailed review of SREBP-1 and FAS in GBM can be found in refs. 32 and 33 .…”
Section: The Four Categories Of Fa Metabolism In Gbmmentioning
confidence: 99%
“…In tumor cells, with the help of ACAT‐1, the cells convert cholesterol to cholesteryl esters and store it in lipid droplets to avoid cytotoxicity induced by high cytoplasm cholesterol level. [ 31 ] It has been shown AVA inhibited tumor proliferation without obvious cytotoxicity to normal cells. [ 32 ] As expected, with EALP treatment, the intracellular cholesterol level was elevated while the content of plasma membrane cholesterol was decreased in B16‐F10 cells as observed by CLSM examination (Figure 3h).…”
Section: Resultsmentioning
confidence: 99%
“…Our ndings are in line with previously published data suggesting lipid metabolic alterations in GBM. [22] In addition, mannitol was upregulated in recurrent tissue compared to the original tumor, suggesting BBB permeability changes after surgical resection and chemoradiation. This may suggest mannitol as a vehicle to guide targeted treatment.…”
Section: Discussionmentioning
confidence: 99%